1982
DOI: 10.1177/1077727x8201000411
|View full text |Cite
|
Sign up to set email alerts
|

Personal Values As An Explanation Of Food Usage Habits

Abstract: This study investigated the existence of a relationship between personal values and consumer food habits, and compared the explanatory power of values with that of life‐style measures and demographics. Personal values were measured in terms of the importance of 20 items selected from England's Personal Values Questionnaire. Life‐ style items reflected frequency of participation in 20 leisure time activities, and demo graphics comprised 22 measures of socioeconomic characteristics and media preferences. Usage r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In addition, some studies have found a within-person approach, rather than an across-person approach, to give more accurate predictions or descriptions of behavior (Contento, Michela and Goldberg, 1988;Davidson and Morrison, 1983). Several studies (Akin et al, 1986;Contento, Michela and Goldberg, 1988;Granzin and Bahn, 1982;Haines, Popkin and Guilkey 1990) examining food consumption patterns or exploring motivation or values behind food use have found cluster analysis useful to identify group characteristics. The revised survey was designed so that cluster analysis could be performed.…”
Section: Revising the Pilot Surveymentioning
confidence: 98%
“…In addition, some studies have found a within-person approach, rather than an across-person approach, to give more accurate predictions or descriptions of behavior (Contento, Michela and Goldberg, 1988;Davidson and Morrison, 1983). Several studies (Akin et al, 1986;Contento, Michela and Goldberg, 1988;Granzin and Bahn, 1982;Haines, Popkin and Guilkey 1990) examining food consumption patterns or exploring motivation or values behind food use have found cluster analysis useful to identify group characteristics. The revised survey was designed so that cluster analysis could be performed.…”
Section: Revising the Pilot Surveymentioning
confidence: 98%